Getting life expectancy estimates right for pension policy - Ayuso, Mercedes (2021)
Ayuso, M., Bravo, J. M., & Holzmann, R. (2021). Getting life expectancy estimates right for pension policy: Period versus cohort approach. Journal of Pension Economics and Finance, 20(2), 212-231. [Advanced online publication on 13 May, 2020]. https://doi.org/10.1017/S1474747220000050 . doi:10.1017/S1474747220000050